A comparative study of carrying angle on sexual dimorphism in young males and females - Maskey, Sunima; Shrestha, Pragya; Mansur, Dil Islam; Shrestha, Sheprala; Shrestha, Nilima; Adhikari, Sabin; Khadka, Bibhuti (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: The carrying angle, the acute angle between the arm and forearm when the upper limb is fully extended and supinated, demonstrates sexual dimorphism and lateral asymmetry. It plays a crucial role in biomechanics and is influenced by various anthropometric factors. This study aims to evaluate the carrying angle in young Nepalese males and females to investigate sexual dimorphism, side differences, and correlations with height, forearm, and arm lengths.Methods: A cross-sectional study was conducted at KUSMS among 160 healthy individuals aged 18–25 years (110 males, 50 females). Carrying angles were measured on both limbs using a manual goniometer. Participants’ height, forearm length, and arm length were recorded. Statistical analysis was performed using SPSS v16.0. Independent and paired t-tests, along with Pearson correlation, were used to analyze sex and side differences and their associations with anthropometric parameters.Results: Females showed significantly higher left carrying angles (8.6°±3.9°) than males (7.3°±3.1°, p= 0.026), while rightside angles were comparable. In males, the right angle was significantly greater than the left (p< 0.001), suggesting lateral asymmetry. Arm length showed a positive correlation with carrying angle in both sexes, more strongly in females (r= 0.408 to0.459). No consistent correlations were found with height or forearm length.Conclusion: This study confirms sexual dimorphism and right-left asymmetry in the carrying angle among young Nepalese adults. Arm length emerged as a statistically significant correlate, particularly in females. These findings underscore the need for population-specific normative data to aid clinical assessments and orthopedic planning.